A combined endoscopic and open surgical approach for chronic retracted proximal hamstring avulsion. Issue 3 (11th October 2019) - Atzmon, Ran; Amar, Eyal; Maor, Dror; Rath, Ehud
Abstract: Proximal hamstring avulsion is an uncommon injury which usually requires surgical intervention. When possible, primary surgical fixation is recommended. In chronic hamstring avulsion with significant retraction of the tendon, hamstring reconstructions using an autograft or allograft are required in order to bridge the gap. This is mainly performed using an open surgical technique. We describe a combined endoscopic and open surgical approach to hamstring reconstruction surgery.